Pengaruh Net Profit Margin (NPM) Dan Debt To Assets Rasio (DAR) Terhadap Return Saham - Lusi Noviyanti; Moh. Wahyudin Zarkasyi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of Net Profit Margin and Debt to Assets Ratio on Stock Return. The sampling method using purposive sampling, obtained a sample of 13 companies. The research data uses secondary data, namely from the financial statements of the food and beverage subsector companies listed on the Indonesia Stock Exchange for the 2014-2018 period eith miltiple linear regression analysis testing with the help of SPSS version 22 using teh normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, t test, f test and the coefficient of determination. The examiner shows that partially NPM has no effect on stock returns and DAR has no effect on stock returns. And simultaneously NPM and DAR have no effect on stock returns. Keyboards: Net Profit Margin (NPM), Debt to Assets Ratio (DAR), Stock return